REVIEW: Noted: Proactive on climate change - Thakur Ranjit Singh (Asia Pacific Network, 2012)
Review of: Convenient action: Gujarat's response to challenges of climate change, by Narendra Modi. New Delhi: Macmillan Publishers India Ltd. 2011, 234 pp. ISBN (10) 0230-331920